SPE Asia Pacific Oil &Amp; Gas Conference and Exhibition 2016
DOI: 10.2118/182278-ms
|View full text |Cite
|
Sign up to set email alerts
|

Sand Control in Corrosive and Erosive Downhole Conditions at High Temperatures

Abstract: In many sandstone reservoirs, the production of sand presents a major obstacle to well productivity. The petroleum industry spends millions of dollars each year to prevent and repair sand control problems including reduced production rates, sand bridging, erosion of equipment and sand disposal and removal. Conventional Sand Screen Systems currently available on the market and manufactured mostly by service providers and are predominantly metallic in construction; these conventional screens have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Sand production in oil wells is one of the key problems that plague the safety and efficiency of oil fields. Excessive sand production will cause problems such as wear of the downhole and surface facilities, sand burial in the pay zone, and the reduction in or halting of oil and gas well production [3]. Therefore, effective sand production monitoring technology is key for ensuring oil well safety and long-term production [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Sand production in oil wells is one of the key problems that plague the safety and efficiency of oil fields. Excessive sand production will cause problems such as wear of the downhole and surface facilities, sand burial in the pay zone, and the reduction in or halting of oil and gas well production [3]. Therefore, effective sand production monitoring technology is key for ensuring oil well safety and long-term production [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…1. With regards to the problem of screen failure, previous studies (Jackson and Gundemoni, 2016;Islam and Farhat, 2017) claimed that the erosive wear and failure of metal screens under high temperature, high pressure, and corrosion conditions are related to underground fluid velocity, underground acid environment, screen plugging, and other factors and that a corrosive environment aggravates the failure of a screen. A previous study (Hamid and Ali, 1997;Liu et al, 2009; investigated the erosive wear of slotted screens by sand-laden crude oil and concluded that the erosion rate of the slotted screens was mainly influenced by sand-laden slurry velocity, sand-laden slurry concentration, sand particle size, and erosive angle.…”
Section: Introductionmentioning
confidence: 99%
“…Sand production in the oil & gas industry is an issue of major concern to the operators as it often results in mechanical wear of equipment thus causing; serious problems to equipment integrity, severe consequences on hydrocarbon production rate and increased safety concerns. It costs the industry millions of dollars each year to mitigate and repair sand production problems including sand disposal and removal [4]. Therefore, effective sand monitoring is a prerequisite for sustainable hydrocarbon production and is particularly important towards minimising operational risks and cost.…”
Section: Introductionmentioning
confidence: 99%